Estudo comparativo da resistência à corrosão dos aços inoxidáveis AISI 304 e 444 em soluções detergentes e sanitizantes da indústria de refrigerantes - Giselle Aline dos Santos Gonçalves (2011)
In food industries, the characteristic stainless steel is a material used due its corrosion resistance and easy-cleaning caracteristic, wich avoids microorganisms to accommodate on its surface. The objective in controling microorganisms development on the material is to prevent the transmission of diseases and infections by the contamination or growing of hazardous microorganisms and degradation of materials and/or equipaments by microorganisms. Industrial tanks and pipes made up of stainless steel, wich comes into direct contact with food and beverages, undergo to a cleansing and desinfection process named Clean in Place (CIP).This method consists in the automatic recirculation of a detergent solution for a controled period of time, followed by rinse with potable water and, finally, cleaning with sanitizer solution and after the recirculation process, new rinse is done. Thus, the equipament and surfaces hygienization is acomplished by cleansing and sanitization. This academic work aims to investigate the corrosion resistance of stainless steel,used in food industry, in the presence of detergent and sanitizer solutions used in the CIP procedure, by using electrochemical measurements, tafel analysis and electrochemical impedance espectroscopy. The results show that the corrosion rate mesured in all different conditions is low, meaning that the studied solutions are adequated to be used in the CIP procedure. The AISI 304 steel proved to be more resistant to corrosion when compared to the AISI 444 steel in the electrolytes studied.